Evaluation of annual performance for building‐integrated photovoltaics based on 2‐terminal perovskite/silicon tandem cells under realistic conditions - Dong C. Nguyen; Fumihiro Murata; Kota Sato; Masaya Hamada; Yasuaki Ishikawa (Energy Science & Engineering, 2022)
Abstract The authors optimized the thickness of the layers in the 1.67‐eV‐bandgap‐perovskite sub‐cell of a 2‐terminal perovskite/silicon monolithic tandem solar cell under standard test conditions to get the current matching between the top and the bottom sub‐cells. Based on that optimized structure of the tandem cell, we characterized, calculated, and analyzed the annual output energy and the annual efficiency of the tandem cells on the facades and the rooftop of buildings under realistic conditions composed of module temperature, realistic illumination irradiance, and incident angle directly measured in Gifu, Japan in 2015. Consequently, the obtained annual output energy is 279.52, 238.89, 129.99, and 115.21 kWh/m2 with the corresponding annual efficiency of 22.42%, 19.70%, 10.50%, and 9.19% for the tandem solar cells mounted on the rooftop, the south, east, and west facades of the buildings, respectively. Thus, the rooftop and the south face of the buildings are the preferred directions for the BIPV application to gain higher energy.